Plan estratégico para la compañía de transporte pesado pesadoexpres s.a. del cantón Quevedo, provincia de los Ríos - Figueroa Miranda, Carlos Marcelo (2016)
The title of this research work is "STRATEGIC PLAN FOR HEAVY TRANSPORT COMPANY S.A. PESADOEXPRES CANTON OF QUEVEDO, PROVINCE OF RIVERS "guided the general objective of this research is part of the Development of a Strategic Plan for heavy transport company PESADOEXPRES S.A., Canton Quevedo, Los Rios Province. The methodology used during the development of this work was based on the application of different methods as follows: inductive, deductive, analytical, synthetic, also was necessary to resort to the use of techniques such as observation, survey of employees and one sample of customers of the company and the interview with the Manager of the company. During the process of developing the Strategic Plan for heavy transport company PESADOEXPRES S.A., it was due to meet the following procedure: In the first instance we proceeded to perform the analysis of external factors to the Company, to do an analysis of social, economic, political, technological, environmental and competitive environmental factors and forces Porter of that was done analysis was possible to obtain accurate information about the main opportunities and threats for the company. Secondly the analysis of internal factors of the Company was held, for which an interview was applied to the Manager; Likewise surveys were applied to a sample of 271 external customers and all 16 employees as a result of the study field could be obtained firsthand sufficient information which identified the main strengths and weaknesses of the company. The identification through internal analysis and external the main strengths, weaknesses, opportunities and threats PESADOEXPRES Company was obtained, served us a basis for structuring the SWOT matrix and then the matrix HIGH IMPACT, which was obtained the following strategic objectives: • Attracting more customers and increase sales of services heavy transport company PESADOEXPRES S. A. • Improve knowledge and skills qualities of heavy transport company PESADOEXPRES S. A. • Increase the number of customers through the widely advertise the services offered by the company. • Improve the performance of each employee of the company. At the end of this paper we present a series of conclusions, among which, we note the following: The heavy transport company PESADOEXPRES S.A. It is in the canton Quevedo, Los Rios province, is dedicated to transporting heavy loads, which offers certain advantages over some competitors, so it has earned the trust of its customers. It is concluded that the manager and workers of the company PESADOEXPRES S.A., said that there is a strategic plan that allows you to improve the performance of employees to accomplish the tasks, activities and functions in the company. The internal analysis identified the strengths and weaknesses of the company to develop the EFI array where a value of 2.59 points was obtained, which means that the strengths prevail over weaknesses, therefore it is necessary to establish operational plans to offset the weaknesses and exploit the internal strengths of the company. In the external analysis of opportunities and threats in the environment of the company were detected with the EFE matrix analysis, which gave a value of 2.34 points, and as a result gives us that the company there was obtained a predominance of threats on opportunities. Subsequently, a draft Strategic Plan was developed for the company PESADOEXPRES S.A. And finally the total budget was by a value of $ 9040.00 US dollars, the same to be financed by the company for compliance with the Strategic Plan. Among the recommendations we are: Implement the research company Strategic Plan, to improve the current situation of the company PESADOEXPRES SA, promote greater commitment from employees and thus obtain optimum results in the performance of commercial activity thereof in canton Quevedo, Los Rios province. The Manager of the company PESADOEXPRES S.A., implement the proposal of the Strategic Plan, made in research and thus improve the current situation of the company. Constantly training must be provided to all staff of the company in customer service, human relations, leadership, finance outlined in the proposed training plan. Ensure the full and timely financing of the total budget, in order to implement the Strategic Plan without difficulties of economic resources.